The Seven Sins of Innovation A Strategic Model for Entrepreneurship - Richards, D.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Offers a psychology based model that features seven key determinants of success or failure for innovation and entrepreneurial endeavours. Provides specific recommendations, examples and case studies that demonstrate how individual and group psychology must be engaged effectively to create entrepreneurial cultures capable of powerful innovation.
Keywords: Small business; Management; Industrial management; Leadership; International business enterprises; Entrepreneurship; Small Business; Innovation/Technology Management; Business Strategy/Leadership.; International Business; Entrepreneurship